The Rose Man of Sing Sing : A True Tale of Life, Murder, and Redemption in the Age of Yellow Journalism - Morris, James McGrath (Book collections on Project MUSE., 2003)
Today, seventy-three years after his death, journalists still tell tales of Charles E. Chapin. As city editor of Pulitzer?s New York Evening World, Chapin was the model of the take-no-prisoners newsroom tyrant: he drove reporters relentlessly?and kept his paper in the center ring of the circus of big-city journalism. From the Harry K. Thaw trial to the sinking of the Titanic, Chapin set the pace for the evening press, the CNN of the pre-electronic world of journalism. In 1918, at the pinnacle of fame, Chapin?s world collapsed. Facing financial ruin, sunk in depression, he decided to kill him.